Encouraging Work Productivity Through Minimum Wage Increase: Surabaya City Case Study - Safira, Tina; Yelanita, Verinda; Rohma, Dhaful Oktaviatul; Mauridhoh, M. Masrur; Suparta, I Made (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to analyze the minimum wage increase and its implication on labor productivity in Surabaya City, as well as identify the factors that influence the relationship. This research uses a descriptive qualitative approach and secondary data from official sources such as the Central Bureau of Statistics (BPS). The data analyzed includes UMK trends and labor force data from 2020 to 2024. The results show that Surabaya's MSE has increased significantly in recent years, influenced by factors such as inflation and the cost of living. This increase in UMK has complex implications for labor productivity. On the one hand, it can improve workers' motivation and welfare, but on the other hand, it can be a challenge for UMKM by increasing operational costs. This research emphasizes the need for balanced policies to support economic growth and business continuity, as well as training programs to improve workforce skills.